Conscience Ecologique Et Developpement Durable: Constat Et Défis - Ludovic, EHOUMA Koffi; Hendersonn, N’GUESSAN Kouamé (European Scientific Journal, ESJ, 2016)
The efficient environmental management is a real problem for sustainable development in our countries. From observations, it appears that the destruction of environmental cover is linked to economic growth and a backward thinking that harm the environmental health. To remedy this, an awareness and a profound reform based on an ecological education is needed. This reflection aims at making a contribution to the understanding and promotion of a real policy on environmental health following the development by Edgar Morin.